In Pursuit of the Triple Bottom Line: Economic, Social, and Environmental Commitment at Clif Bar, Stonyfield Farm, and Starbucks - Rainey, Kristen M. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper will analyze three different companies in the food and beverage industry: Clif Bar, Stonyfield Farm, and Starbucks Coffee Company. All three serve as role models to others in pursuit of the triple bottom line: all take into consideration economic, social and environmental returns and have received public recognition for their success in all three areas. The question I seek to answer is whether these companies' social and environmental initiatives make them more profitable. Does Corporate Social Responsibility (CDR) make good business sense?